Przestępstwa gospodarcze z Kodeksu spółek handlowych w świetle danych statystycznych - Ochman, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The aim of the article is to analyze convictions of adults for economic crimes in the Commercial Companies Code. The analysis concerns both the structure of convictions and their dynamics in the field of convictions in general, as well as the structure of punishments for crimes. An attempt is also made to explain the trends in this area.
Keywords: przestępczość gospodarcza; prawo karne gospodarcze; kodeks handlowy; dane statystyczne